Expressions of travelling in the portuguese 'romanceiro' - Boto, Sandra (2012)
Travel themes in the Portuguese romances from the modern oral tradition are explored, supported by Di Stefano's concepts of romance omega and romance alfa. They can refer to past events not in the present narrative, but suggested by present events or by lhe characters' role or nature (a soldier that returns from war, for example). But travel can also assume a more direct role in the alfa type, as the narrative structure corresponds directly with the events narrated. Travel action, therefore, collides with the narrative present, and is reflected in a related detailed verbal structure.